IMPROVING STUDENTS’ WRITING SKILL IN ARGUMENTATIVE TEXT THROUGH PICTURE WORD INDUCTIVE MODEL (PWIM) AT TWELVE GRADE OF SMA NEGERI 4 PEMATANGSIANTAR - Juni Sari Sianturi; Aulia Monica Tambunan; Elisabeth Dwi Clara; Daniel Binsah Lumbangaol; Dumaris Elseria Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study aimed to investigate the effectiveness of the Picture Word Inductive Model (PWIM) in improving students’ writing skills in argumentative texts at the twelfth grade of SMA Negeri 4 Pematangsiantar. The study was conducted in response to students’ difficulties in generating ideas, organizing arguments coherently, and applying appropriate grammatical structures in argumentative writing. The Picture Word Inductive Model was implemented as an instructional strategy to help students develop vocabulary, construct ideas systematically, and improve their writing organization through visual stimuli. This research employed a quantitative approach using a quasi-experimental design involving two groups: class XII-6 as the experimental group taught using the Picture Word Inductive Model and class XII-8 as the control group taught using conventional teaching methods. Data were collected through pretest and post-test writing tasks assessed using an analytical scoring rubric covering content, organization, vocabulary, language use, and mechanics. The findings revealed that the mean score of the experimental group increased significantly from 51.39 in the pre-test to 74.58 in the post-test, while the control group showed a smaller improvement from 54.17 to 65.97. The result of the t-test analysis showed that the obtained t-value (12.88) was higher than the t-table value (1.99) at the 0.05 significance level, indicating a statistically significant difference between the two groups. These findings suggest that the Picture Word Inductive Model effectively improves students’ argumentative writing skills by enhancing idea development, vocabulary mastery, and text organization. Therefore, PWIM can be considered an effective instructional model for teaching argumentative writing in EFL classrooms. Keywords: Writing skills; Argumentative text; Picture Word Inductive Model; EFL learning; quasi-experimental research